Molecular Genetics of Esophageal Cancer : Indian Perspective - Ray, Suddhasattwa; Malekzadehmoghani, Mona; S Ray, Sonia; Sen, Partha; Chakraborty, Sayan (Asian Pacific Journal of Cancer Biology, 2021)
Background: RIZ1 is one of the tumor-suppressor genes that is silenced in many human cancers. Change in RIZ1 expression has not been reported in ESCC patients. Therefore, the aim of this study was to investigate the role of RIZ1 in ESCC in the Indian population. Methods: Twelve esophageal squamous-cell carcinoma (ESCC) patients in stage IV and 12 healthy individuals were used in this study. Tissue sampling was taken from individuals and total RNA was isolated and then cDNA was synthesized using PCR. RIZ1 primers were then designed, and RIZ1 expression was quantified by qRT-PCR. Mapping of CpG islands in RIZ1 promoter was performed using bioinformatics tools. The promoter methylation status of this gene was studied using u methylation-specific PCR (MSP). T-student test was used to analyze the data. Results: Decreased RIZ1 expression was observed in ESCC compared with healthy controls. The results showed a relatively higher density of CpG dinucleotides in the RIZ1 promoter. No significant difference in promoter methylation was observed in blood and tissue samples. Conclusion: The study showed a significant down-regulation of RIZ-1 gene in the blood and tissue samples of ESCC patients that did not related to the altered promoter methylation.